2013
DOI: 10.1177/0143034312469304
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gypsy children’s conceptions of learning: A phenomenographic study

Abstract: In Portugal, as in other European countries, gypsy children remain largely at the margins of the educational system. Their underachievement and the associated dropout rates from school are serious educational issues and factors contributing to their marginalization in society. However, there is limited research qualitatively examining the different ways in which gypsy children think about learning. The current study examined data provided by 26 Portuguese gypsy elementary school children ranging from 9- to 13-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…The population of the study was from lower socio-economic background. This socioeconomic background is linked to undesired conceptions of learning (Rosário et al, 2014). The study affirmed the findings of Rosário et al (2014).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The population of the study was from lower socio-economic background. This socioeconomic background is linked to undesired conceptions of learning (Rosário et al, 2014). The study affirmed the findings of Rosário et al (2014).…”
Section: Discussionsupporting
confidence: 78%
“…A qualitative study by Rosário et al (2014), revealed that students perceive their learning process in view to their learning activities at school. Likewise, the process and approach opted to evaluate students' learning in schools inspire students' to conceive learning in particular ways.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The study adopted a In recent years, more phenomenographic studies have focused on highlighting children's views, opinions, and experiences (e.g. Karrby, 1990;Mumtaz, 2002;Rosário et al, 2013).…”
Section: The Studymentioning
confidence: 99%
“…The study adopted a In recent years, more phenomenographic studies have focused on highlighting children's views, opinions, and experiences (e.g. Karrby, 1990;Mumtaz, 2002;Rosário et al, 2013).A group of sixteen upper primary children between the age of eight and eleven years old participated in the study. The study was conducted over a period of three years; the first year was the conceptualizing and preparation period that involved reviewing relevant literature, critical discussion of methodologies, and piloting interview questions with upper primary children in Brunei to explore their thoughts about learning in government schools; the second year comprised refinement of interview questions using the scenario-based approach and data collection; and finally, the third year was the period of data analysis and interpretation of findings.…”
mentioning
confidence: 99%